Partição da energia e exigências nutricionais no terço final da gestação e avaliação do perfil metabólico durante o período de transição de vacas Gir e F1 holandês x Gir - Helena Ferreira Lage (2015)
Given the lack of scientific literature about the energy metabolism of Gir and F1 Holstein x Gir cows (F1 HXG), especially about pregnancy data, two experiments were developed using six Gir cows (average initial of 435.16 kg) and F1HxG six cows (average initial weight of 515.60 kg). The first chapter there is a review about the development of pregnancy and its impact on energy metabolism ruminant females. The second chapter presents energy partition data of these animals on 180, 210 and 240 days of gestation obtained by respirometry. The animals received diet in a restricted amount, equivalent to 1.30 times the net energy requirement for maintenance. The higher dry matter intake (P <0.05) of F1HxG cows was reflected in the consumption of other dietary nutrients, such as organic matter (OM), insoluble fiber neutral detergent corrected for ash and protein (NDFap), expressed as kilograms per day (kg / d). Variables such as daily intake (kg / day) of ether extract (EE), crude protein (CP) and total digestible nutrients (TDN) showed superiority (P <0.05) for the F1 H x G cows only at 210 and 240 days of gestation. In general, however, it notes that the higher consumption by crossbred cows at any gestational age was responsible for changes in digestibility of any nutrients (P> 0.05) except for CP. Evaluating the dietary energy concentration comparisons were made with the values obtained by equations of NRC (2001) to estimate the energy concentration of the diet. Only the equation (2-2) of the NRC (2001) was efficient in predicting the concentration of metabolizable energy (ME) from the digestible energy (DE). The concentration of ED diet did not differ (P> 0.05) between genetic groups and periods, with average value of 3.25 Mcal / kg MS. The ME concentration of the diet ranged between 2.55 and 2.82 Mcal / kg MS among periods and genetic groups evaluated. The average level of net energy (NE) of diets consumed by experimental cows was 1.47 Mcal / kg MS. Energy partition data proved that the diet fed to cows at 180, 210 and 240 days of gestation was enough to meet the energy requirement of the animals. The proportion of gross energy (GE) lost as feces did not differ between the evaluated races and corresponded on average to 28.65%, reflecting the values reported for the digestibility. The daily methane production (L / day) followed the pattern described for dry matter intake, with higher production for (P <0.05) F1 HXG when compared to Gir animals. However when expressed in L / kg DM or as percentage of EB intake (mean 6.44%), no differences were observed between the genetic groups (P> 0.05). The daily loss of energy as urine (mean value of 1.42 Mcal / day) did not differ (P> 0.05) between genetic groups and oscillated between 3.87 to 5.35% of the EB ingested. The ME ingested by F1 HXG animals was higher (P <0.05) at all times evaluated when compared to Gir cows when expressed in Mcal / day. When expressed in kcal / kg of metabolic body weight (MW), however, the intake was 11% higher (P <0.05) in the crossbred cows only after 240 days of gestation and averaged 194.39 Kcal / kg MW. Gir cows showed no change in the ME intake among the three time periods (P> 0.05), with an average of 146.66 kcal / kg MW. Fractionation of ME to pregnancy was obtained by deducting from the ME intake value the maintenance ME requirements described by Lage (2011) of 120.05 and 146.06 kcal / kg MW for the Gir and F1 HxG animals, respectively. The average consumption of ME for pregnancy in this study was 5.33 for cows F1 H x L and 4.46 Mcal / day for Gir cows, respectively. The percentage of ME in relation to GE (or q, which correspond to the metabolizability of the diet) was similar among the evaluated genetic groups (P> 0.05): 0.60. The average ratio ME / DE obtained was 0.84 between the races and periods evaluated. The heat increment accounted for of 24.38% of GE intake for Gir cows and 22.74% for F1 H x G cows. The maintenance data presented by the experimental animals were calculated based on the values reported by Lage (2011 ) of 92.02 kcal / kg MW for F1 HxG cows and 76.83 kcal / kg MW for Gir cows (both non-pregnant). The proportion of GE intake used to the basal metabolism by pregnant cows in this study did not differ between the races and the evaluation period and corresponded for 29.69%. The mean net energy for pregnancy was of 2.76 Mcal / day and did not differ between groups and periods (P> 0.05). The conversion efficiency of ME into NE for pregnancy obtained in this study was 13.00%. The third chapter present data regarding to the metabolic profile of Gir and F1 Holstein x Gir cows in the transition period (30 days before and 28 days after delivery), using the same animals described in energy metabolism trial. The following parameters were evaluated: plasma glucose, non-esterified fatty acids (NEFA), cholesterol, triglycerides, blood urea nitrogen (BUN), creatinine, total protein, albumin, calcium and aspartate aminotransferase (AST). The results demonstrate the proper functioning of homeostatic and homeorretic mechanisms of Gir and F1 Holstein x Gir cows used in this experiment during the transition period. The mobilization of skeletal muscle tissue could be verified by the rise in BUN levels and decreased creatinine concentration and nitrogen close to parturition. The mobilization of adipose tissue was confirmed by the drop in triglyceride levels and increased non-fatty acids (NEFA) close to delivery, especially in F1 H x G cows. The interpretation of the data implied that tissue mobilization was responsible for maintenance of normal blood glucose levels during the transition period. The classic drop in plasma glucose concentration near to parturition, usually seen in specialized dairy cows was not observed in this study possibly due to lower milk potential of the animals used. The normal glucose, cholesterol, albumin and total protein are indicative of the absence of severe liver injuries in experimental animals, which can beevidenced by the normality of the enzymatic activity of AST throughout the experimental period.